PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN CAT MERK TOA PADA CV. ANUGERAH PRATAMA SEMARANG - Alwin Basri; Fidyah Yuli Ernawati; Jefri Heridiansyah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract Purchase decision is a form of consumer behavior in using a product. The purpose of this study was to determine the effect of Product Quality, Price and Promotion on the Purchase Decision of TOA Brand Paint on CV. Semarang Primary Award. The population in this study were consumers of CV. Anugerah Pratama Semarang in Semarang City in semester 1 of 2020. The sample in this study used accidental sampling so that a sample of 60 consumers was obtained. The dependent variable in this study is Purchase Decision, the independent variables are Product Quality (X1), Price (X2) and Promotion (X3). The method of analysis used multiple linear regression analysis. Based on the results of data analysis, it is concluded that product quality has an effect on purchasing decisions with a significance value of 0.000 < 0.05. Price has no effect on purchasing decisions with a significance value of 0.217 > 0.05. Promotion has an effect on purchasing decisions with a significance value of 0.000 <0.05. The value of the coefficient of determination is 68.4%. Suggestions that can be given to producers are to pay attention to product quality and promotion because these two variables influence consumer purchasing decisions. For further researchers to add independent variables so that the value of the coefficient of determination increases further.